2018
DOI: 10.1097/gox.0000000000001791
|View full text |Cite
|
Sign up to set email alerts
|

McKissock’s Reduction Mammaplasty Revisited: A Case Series Study with 12-months Follow-up

Abstract: Supplemental Digital Content is available in the text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 21 publications
1
1
0
Order By: Relevance
“…Gaye 24 and Palvé 26 report in their respective studies a predominance of bilateral gigantomastia. The mean breast axis in our study is similar to that reported by Abozeid, 27 in a case series study with 12-month follow-up of the Mac Kissock reduction plasty revisited, who found a similar result, i.e. 34.12 cm, thus reflecting the size of the gigantomastia.…”
Section: Commentssupporting
confidence: 90%
“…Gaye 24 and Palvé 26 report in their respective studies a predominance of bilateral gigantomastia. The mean breast axis in our study is similar to that reported by Abozeid, 27 in a case series study with 12-month follow-up of the Mac Kissock reduction plasty revisited, who found a similar result, i.e. 34.12 cm, thus reflecting the size of the gigantomastia.…”
Section: Commentssupporting
confidence: 90%
“…The mean duration of the procedure was 62.12 ± 10.3 minutes, which is the shortest among the other studies [ 1 32 ]. The majority of studies reported operative times ranging from 2 hours [ 20 , 27 , 28 ] to almost four hours [ 17 29 ]. It is widely recognized that an extended operative time is associated with an increased risk of various complications, regardless of whether low or high-intensity electrocautery is utilized [ 8 31 ].…”
Section: Discussionmentioning
confidence: 99%